Financial Aspects Of Biogas Production From Livestock Waste To Meet Household Energy Needs - Bambang Singgih; Budi Triono; Nurul Rusdi; Muhammad Ulinuhayani; Permana Nurhidayat; Muchdar Soedarjo (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
The livestock sector has significant potential to contribute to methane emissions, which are the second largest after CO2, accounting for 13% of total emissions. One solution to control methane emissions is the use of biogas reactors. This study aims to assess the financial aspects of biogas production from livestock waste to meet household energy needs and to determine its financial feasibility. The research employs a qualitative approach that emphasizes flexibility, direct interaction with research subjects, and sensitive interpretation of data context. Data collection was conducted through a literature review by examining and analyzing literature related to the research topic. The literature study results indicate that constructing biogas reactors using cow dung has viable potential for development, especially as a replacement for LPG. However, replacing wood fuel depends highly on the local price of firewood. This study recommends that, for the development of biogas from cattle farm waste to replace firewood, interest subsidies or other assistance are needed to make the development feasible. Additionally, to encourage public interest in developing biogas reactors for cattle farm waste, financial incentives in the form of interest subsidies through program loans are necessary. Developing biogas reactors from cattle farm waste for household energy needs is economically viable, especially as a substitute for LPG, but requires additional support such as interest subsidies to replace firewood. Financial incentives are essential to attract public interest in developing these biogas reactors.